Constructing Beauty: The Photographs Documenting the Construction of the Bloor Viaduct - Rodgers, Anastasia (Archivaria, 2002)
This article is a case study that focuses on selected photographs taken by the late City of Toronto photographer Arthur S. Goss which document the construction of the Bloor Viaduct. The paper considers the importance of the political/bureaucratic context in which the photographs were taken and how this knowledge may affect the interpretation and appreciation of the photographic narrative. This paper contends that the City of Toronto's civic agenda in creating this photographic series -- to record construction progress and illustrate the growth of the City -- is just one part of the entire narrative, and it is when archivists and researchers take the functional context of creation into consideration that they can use the photographs for supplying a part of the story most effectively. RÉSUMÉ Cet article est une étude de cas mettant l'accent sur une sélection de photographies prises par le défunt Arthur S. Goss, photographe de la ville de Toronto, et portant sur la construction du viaduc Bloor. L'auteure examine l'importance du contexte politique et bureaucratique entourant la prise des photographies et se demande comment cette connaissance peut modifier l'interprétation et la compréhension de la narration du récit photographique. L'article soutient que l'objectif de la ville de Toronto en créant la série de photographies, c'est-à-dire documenter le progrès de la construction et illustrer la croissance de la ville, ne reflète qu'une partie du récit des faits et que ce n'est que quand les archivistes et les chercheurs prennent en compte le contexte fonctionnel de la création que les photographies peuvent le mieux être utilisées pour éclairer une partie de l'histoire.